(untitled) (Eurasian Medical Research Periodical, 2022)
The first cases of human infection with a new coronavirus infection, called "Corona Virus Disease 2019" (COVID-19), appeared in late 2019 - early 2020 in Wuhan (China). At the time of writing this review, more than 6 million cases and more than 400 thousand deaths have been registered worldwide. During this time, a large number of articles have appeared describing the diagnosis, pathogenesis, clinic and therapy of this disease. This review is devoted to the complication of coronavirus infection bronchopneumonia.